Abdominal Migraine among Children in Diyala Province - Shihab Khleel , Dhay; Ghazal Noaman, Nadhim; Othman Habeeb , Hailah; Mokheiber Mostafa, Falah (Diyala Journal of Medicine, 2022)
Background: Abdominal migraine is characterized by frequent, paroxysmal, and acute attacks of abdominal pain. There are many hypotheses which contribute to its pathophysiology, but abnormal gastric motility can play a role in the disease's pathogens. Abdominal migraine affects 0.2% to 4.1% of children. Diagnosis of abdominal migraine depends on history and physical examination, radiological and laboratory tests which help to exclude other causes of abdominal pain. Treatment is focused on non-pharmacological and pharmacological therapy. Objective: To identify abdominal migraine among children in Diyala province and summarize the relationship between abdominal migraine and other disorders. Patients and Methods: A cross-sectional study was carried out in Al-Batool teaching hospital in Diyala Province for 8 months from 1st November 2020 till 30th June 2021. The target population was the children who were attending pediatric consultant clinics who were examined and recorded according to Rome Ⅳ Criteria for diagnosis of abdominal migraine. A total of 300 children were included in the study. The information was taken from mothers of children using a questionnaire that was used for the study of abdominal migraine. All data were collected by introducing and analyzing information by using computer (Microsoft Excel 2010 software for windows). Statistical analysis was done by number and percentage as description. Results: The results of demographic data were conducted on 300 child their ages ranged between 3-15 years presented with paroxysmal abdominal pain associated with at least two of following features as anorexia, nausea, vomiting, headache , palpitation , decrease school performance and pallor . Peak percentage of abdominal migraine was seen in age between 6-9years (54.7%). Females affected nearly equal to males, females were (51.6%) and males were (48.3%). Regarding the location of abdominal pain, it occurred mainly in periumbilical site (80%). In children with abdominal migraine, there was history of migraine headache and motion sickness in first-degree relatives. There were many triggering factors for abdominal migraine such as foods like sweets, chinese food, carbonated drinks which were found in (90.3%) of children and watching TV, mobile,and electronic games for long time in (96.7%) of children. The duration of symptoms less than 6 months was seen in (13.3%) of children while the duration of symptoms in between 6-12 months was seen in (60%) of children while the duration of symptoms above one year was seen in (26.7%) of children . Conclusion: Abdominal migraine was mostly seen in school age children. Family education about the causes ,trigger factors and management of disease is important.